DEVELOPMENT OF EXTENDED-RELEASE ANAGRELIDE TABLETS: A FORMULATION AND DISSOLUTION STUDY - Seyedeh Shima Jalilimagham; Alireza Dabirsiaghi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Anagrelide immediate release is commonly used multiple times a day for patients with thrombocythemia. However, frequent dosing can lead to potential dose-related side effects. The purpose of this study was to formulate an extended-release of anagrelide by the matrix manufacturing method to be compressed into tablets and compare its release profile with the reference patented formulation. The wet granulation method was utilized to produce the extended-release tablet. Different formulations of anagrelide tablets containing HPMC, ethyl cellulose, and other excipients were prepared. Flow characteristics and quality control tests including Carr’s index, Hausner’s ratio, hardness, thickness, weight variation, content uniformity, as well as dissolution test were conducted using HPLC analysis. Finally, results were compared with the patent release profile as a reference. Through a series of pre-formulation studies and dissolution tests, it was determined that the F5 formulation, with an optimized balance of HPMC, ethyl cellulose, and other excipients, achieved a drug release profile similar to the reference patent formulation. The F5 formulation showed sustained release of anagrelide over the desired period, making it a promising candidate for further clinical evaluation. Further studies are needed to assess the pharmacokinetic profile and efficacy of the F5 formulation in patients with essential thrombocythemia.